Self-monitoring of blood pressure for preeclampsia patients: Knowledge and attitudes - Johanna Munyungula; Simangele Shakwane (AOSIS, 2021)
Background: Preeclampsia is one of the causes of maternal deaths and is also responsible for complications such as premature births worldwide. In South Africa, hypertensive disorders cause 14% of all maternal deaths. Evidence indicates that it may be beneficial to empower women to monitor their blood pressure (BP) in the comfort of their homes. Objectives: The purpose of this study was to explore and describe preeclampsia patients' knowledge and attitudes towards the self-monitoring of their BP. Method: An exploratory, descriptive and contextual qualitative research study was conducted. Fourteen preeclampsia patients were purposively sampled and participated in the study. In-depth semi-structured interviews were used to collect data. Data were analysed using the thematic analytic approach. Results: The knowledge and attitudes towards the self-monitoring of blood pressure (SMBP) were explored. Four themes emerged, namely understanding of hypertension disorders during pregnancy, openness on self-monitoring at home, its hindrances and benefits. The participants portrayed limited understanding and knowledge of preeclampsia, yet they had positive attitudes towards monitoring BP themselves and were open and willing to do self-monitoring at home. Conclusion: The use of SMBP may relieve overcrowding in public healthcare institutions. Encouraging patients to participate in self-monitoring could promote active participation and a positive outlook on their pregnancies. The unavailability and unaffordability of the equipment may pose a challenge to women with a low socioeconomic status.